Implementasi Quantum Teaching PAI Dalam Meningkatkan Kreatifitas Belajar - Fitriono, Ahmad Natsir; Fatahuddin (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2024)
Islamic Religious Education taught in schools should be able to emphasise the cognitive aspect and being able to encourage and move Islamic Religious Education teachers to be more careful in which developing Islamic Religious Education learning that is oriented toward value education (affective). Islamic Religious Education should be able to practice its education in the emphasis on cognitive aspect in growing religious awareness, must be able to touch the affective and conative-volutive aspects, namely the willingness and awareness to practice the values of Islamic teachings. The problem that arose in the learning of Islamic religious education are capable of creating innovation in the growth of students' awareness. Innovation is needed in the implementation of learning in order to create students who are touched by affective and conative-volutive aspects. This article tries to explore the right approaches and method in teaching and learning activities that exist so far, where teachers are always positioned as the only source of obtaining information (teacher-centred) and students are passive in seeking and processing this information, by getting used to student creatively (student-centred) constructing their own understanding through their learning activities.